A Pilot Metabolic Profiling Study of Patients With Neonatal Jaundice and Response to Phototherapy. Issue 4 (15th June 2016) - Cai, A; Qi, S; Su, Z; Shen, H; Yang, Y; Cai, W; Dai, Y
Abstract : Phototherapy has been widely used in treating neonatal jaundice, but detailed metabonomic profiles of neonatal jaundice patients and response to phototherapy have not been characterized. Our aim was to depict the serum metabolic characteristics of neonatal jaundice patients relative to controls and changes in response to phototherapy. A 1 H nuclear magnetic resonance (NMR)‐based metabonomic approach was employed to study the metabolic profiling of serum from healthy infants ( n = 25) and from infants with neonatal jaundice ( n = 30) pre‐ and postphototherapy. The acquired data were processed by multivariate principal component analysis (PCA) and orthogonal partial least‐squares‐discriminant analysis (OPLS‐DA). The PLS‐DA and OPLS‐DA model identified nine metabolites capable of distinguishing patients from controls. In addition, 28 metabolites such as β‐glucose, α‐glucose, valine, and pyruvate changed in response to phototherapy. This study offers useful information on metabolic disorders in neonatal jaundice patients and the effects of phototherapy on lipids, amino acid, and energy metabolism.